2020
DOI: 10.1186/s12985-020-01463-2
|View full text |Cite|
|
Sign up to set email alerts
|

Toll-like receptor-mediated innate immunity against herpesviridae infection: a current perspective on viral infection signaling pathways

Abstract: Background In the past decades, researchers have demonstrated the critical role of Toll-like receptors (TLRs) in the innate immune system. They recognize viral components and trigger immune signal cascades to subsequently promote the activation of the immune system. Main body Herpesviridae family members trigger TLRs to elicit cytokines in the process of infection to activate antiviral innate immune responses in host cells. This review aims to clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 244 publications
0
22
0
Order By: Relevance
“…The Toll-like receptors (TLRs) family is a group of membrane receptors found mainly in the immune system and correlated to inflammation during viral infection and tumorigenesis [ 92 , 93 , 94 ]. Among other receptors, HA binds the TLR4 promoting tumor growth and differentiation.…”
Section: Hyaluronan In Tme: a Simple Extracellular Macromolecule With A High Impact In Tumor Progressionmentioning
confidence: 99%
“…The Toll-like receptors (TLRs) family is a group of membrane receptors found mainly in the immune system and correlated to inflammation during viral infection and tumorigenesis [ 92 , 93 , 94 ]. Among other receptors, HA binds the TLR4 promoting tumor growth and differentiation.…”
Section: Hyaluronan In Tme: a Simple Extracellular Macromolecule With A High Impact In Tumor Progressionmentioning
confidence: 99%
“…Moreover, it was reported that del-LMP-1 without well-characterized CTAR1 and CTAR2 domains, which are important for the activation of NF-kB pathways, revealed decreased efficacy in lowering TLR9 level. The relationships presented by the researchers showed the consequences of the activation of the NF-kB pathway through the mechanism used by LMP-1 to regulate TLR9 expression [18,29,36].…”
Section: Discussionmentioning
confidence: 99%
“…Various researches revealed that TLR9 are important factor mediating interaction between EBV and the host immune response [17,18]. Moreover, during viral infections, the role and response of TLR may influence transformation to malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings have potential implications for HCMV-related kidney disease. As in other infectious pathogens, the innate immune responses to CMV are thought to be triggered by pathogen-associated molecular patterns that engage pattern recognition receptors including Toll-like receptors (TLRs), resulting in the release of anti-viral and pro-inflammatory cytokines (West et al, 2012;Zheng et al, 2020). Frascaroli et al analyzed TLR genotypes and responses in immunocompetent patients with primary symptomatic HCMV infection presenting as mononucleosis.…”
Section: Innate and Adaptive Immune Control Of CMV Pathogenesismentioning
confidence: 99%